2018
DOI: 10.2147/dddt.s154660
|View full text |Cite
|
Sign up to set email alerts
|

Tendinopathy: injury, repair, and current exploration

Abstract: Both acute and chronic tendinopathy result in high morbidity, requiring management that is often lengthy and expensive. However, limited and conflicting scientific evidence surrounding current management options has presented a challenge when trying to identify the best treatment for tendinopathy. As a result of shortcomings of current treatments, response to available therapies is often poor, resulting in frustration in both patients and physicians. Due to a lack of understanding of basic tendon-cell biology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
112
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 133 publications
(187 reference statements)
1
112
0
12
Order By: Relevance
“…Few tendon-specific markers have been identified. Col-1a1 and Col-3a1 are considered to be the main tendon collagen in matrix [5], especially Col-1a1 which has often been used as a tendon-associated marker in tenogenic differentiation study [13,25]. Tnmd is a member of type II transmembrane glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few tendon-specific markers have been identified. Col-1a1 and Col-3a1 are considered to be the main tendon collagen in matrix [5], especially Col-1a1 which has often been used as a tendon-associated marker in tenogenic differentiation study [13,25]. Tnmd is a member of type II transmembrane glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is tendon injury prevalent, it is also a tough clinic problem, due to its hard healing process because of hypovascularity and hypocellularity [3]. Many attempts, such as autologous grafting, application of growth factors and gene therapy, have been made to repair the injury, but often following the dysfunction of the donor site and a long and poor recovery [4,5]. Therefore, the treatment strategy to repair tendon injury still needed to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, absenteeism due to lateral epicondylitis (tennis elbow) alone, is approximated to cost ÂŁ27 million per annum (Walker-Bone et al, 2012). Furthermore, tendons and ligaments heal poorly frequently resulting in months of disability and weaker tendon(s) that are more susceptible to future injuries (Lipman et al, 2018;Riley, 2008). Despite our increased understanding of tendon biology and tendon repair mechanisms, we are yet to develop effective treatment strategies, and surgical outcomes are often poor (Coghlan et al, 2008;James et al, 2008;Kukkonen et al, 2014;Liu et al, 2008;Vitale et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Tendinopathy accounts for about 30% of all musculoskeletal complaints in a general practice setting [ 1 ]. Both acute and chronic tendinopathy cause pain and morbidity, and may require long and expensive treatments including joint replacement [ 2 ]. Recent studies have revealed the presence of a stem cell population within tendons [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%